2018
DOI: 10.1111/jog.13659
|View full text |Cite
|
Sign up to set email alerts
|

Association between expression of MMP‐7 and MMP‐9 and pelvic lymph node and para‐aortic lymph node metastasis in early cervical cancer

Abstract: MMP-7 and MMP-9 expressions were associated with lymph node metastasis in patients with early cervical cancers, suggesting a positive correlation of MMP-7 and MMP-9 with invasive potential in early cervical cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…We found comparable results in the studies of Li et al, 23 but those authors observed significantly higher expression of MMP-9 in CC tissues. Similar results were demonstrated by Guo et al, 33 where MMP-9 expression was associated with lymph node metastasis and suggested an invasive potential in early CC. Some researchers have demonstrated the statistical significance of VEGF expression in CC tissues.…”
Section: Discussionsupporting
confidence: 89%
“…We found comparable results in the studies of Li et al, 23 but those authors observed significantly higher expression of MMP-9 in CC tissues. Similar results were demonstrated by Guo et al, 33 where MMP-9 expression was associated with lymph node metastasis and suggested an invasive potential in early CC. Some researchers have demonstrated the statistical significance of VEGF expression in CC tissues.…”
Section: Discussionsupporting
confidence: 89%
“…It was reported that blocking Snail expression inhibited the activity of MMP-9 in ovarian cancer cells 46 . MMP-9 belongs to the family of matrix metalloproteinases, and its expression is positively correlated with the invasive potential of cervical cancer 47 . Here, we detected an increased expression of Snail and MMP-9 decreased expression of E-cadherin when PRDX1 was overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated MMP-9 expression and/or activity causes cellular invasiveness and leads to the growth and clinical progression of a wide variety of human cancers [ 10 , 14 , 15 , 16 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Mmp-9 Production or Activity Is Regulated At Multiple Levmentioning
confidence: 99%
“…The role that MMP-9 has in the development of the primary tumor has been described elsewhere [ 14 , 15 , 16 ]. Herein, the available scientific literature concerning the impact that the deregulated expression or activity of MMP-9 might exert on solid tumor metastases is reviewed in the context of a Special Issue of the International Journal of Molecular Sciences, entitled “Tumor Cell Invasion and Metastases”.…”
Section: Introductionmentioning
confidence: 99%